(-3i)(4i)(-5i)=

Simple and best practice solution for (-3i)(4i)(-5i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-3i)(4i)(-5i)= equation:


Simplifying
(-3i)(4i)(-5i) = 0
Remove parenthesis around (-3i)
-3i(4i)(-5i) = 0
Remove parenthesis around (4i)
-3i * 4i(-5i) = 0
Remove parenthesis around (-5i)
-3i * 4i * -5i = 0
Reorder the terms for easier multiplication:
-3 * 4 * -5i * i * i = 0
Multiply -3 * 4
-12 * -5i * i * i = 0
Multiply -12 * -5
60i * i * i = 0
Multiply i * i
60i2 * i = 0
Multiply i2 * i
60i3 = 0
Solving
60i3 = 0
Solving for variable 'i'.
Move all terms containing i to the left, all other terms to the right.
Divide each side by '60'.
i3 = 0.0
Simplifying
i3 = 0.0
The solution to this equation could not be determined.

You can always share this solution

See similar equations:

| 2x+10y=-100 | | .5-6m=.1m-4 | | .90x+.5(18-x)=.10(-144) | | 2x+10y=100 | | x-(-32)=4 | | 2-7x^2=6x+3 | | 0.5-6m=0.1-4 | | 3(2d+1)=9 | | 3x-10=5+9 | | 36+x=70 | | 36+x=30 | | 107-5x=31x+15 | | 1.2x-7=6x-16.6 | | n+2=206 | | .4x+.16(20-x)=20(.22) | | 7=3y-3-(y-2) | | z=9x+12y | | 1-2(x-4)+1=2/3+4 | | 5-3(2x-1)=4x-22 | | n+1=57 | | 5+17=23 | | x+5x+(5x+4)=99 | | 1000x+200=640 | | 1.5(4z+0.25)=2(z+0.0625) | | 5(x+4)-2(7-2x)=3(2x+3) | | 3/2*(x+4)+1=1/3+x+2 | | 2.59c=1.48 | | 306=x^2 | | -2(7-y)+13=y | | .08x+.06(1800-x)=1290 | | .96x=46 | | 5(2x-3)+11=6x | | 1350=.7x | | c+2.59=1.48 | | 6x=3y | | 8T+5=6T-1 | | x=8-13 | | 30+65x=160 | | (x-2)(x+2)=x^2-4 | | 100,1567913-(100-x)*0,867095741-x=0 | | 3-4y=-25 | | 12-(4x+5)=7+x | | 69-7x=11x-17 | | -17+23=-4-8b | | w+3(2)=4w | | 3x=18x | | 3(a+4)=21 | | 10-7x=165-42x | | 65x=65 | | 12-10x=176-38x | | 2t-4=s+4t | | 3x+14=5(6+x) | | 5x+(13.4-2x)=16.4x | | 6x-2=14x+54 | | 8x^3-10x^2-7x-1=0 | | x*3+1=7 | | y-(2)=9(x-2) | | 5x+7=113-10x | | x^2-10x-39= | | 6y-72=4y-56 | | 3/5(1+p)=21/20 | | p^2+9p+27=0 | | ln(x-6)+ln(x+5)=ln(x-31) | | -30-3x=12-3x | | -3x-8+4=7 |


Related pages


200 000 euros to dollarsgreatest common factor of 72 and 54find gcf and lcm calculatorsquare root of 10891921 in roman numerals2x 5y 163y 5x91.1xfactoring calculator with stepsroman numerals for 19781.3125 as a fractionwhat is 0.875 as a fraction40-6-711 cos 6xderivative sin 2 x6x 2x 1roman numerals 6511 000 pounds in dollarswrite 0.4 as a fractionintegrating sqrt 1 x 2differenciation calculator6u8square root of 2.56prime factors of 240square root of 484722.52what is the greatest common factor of 72 and 54what is prime factorization of 96how to solve a 5x5cosx 2sinx 1 02sinx cosxequations solver with stepsfraction multiplier calculatorwhat is the prime factorization of 6843 8 decimal form87-414y 2x 150derivative 5xhow to factorise 3x 12secx cosx sinxlog3x 43x-6 factored0.125 in fractionhcf of 72 and 96y 3x 3 graphderive cos 2x3x 5y 161992 roman numeralsderivative of ln 2x 1derivatice calculator5000 roman numerals2xy xy0.6875 as a fraction3squaredroman numerals for 1963tan30prime factorization of 56170 prime factorizationfactor 6x 2 7x 2equation solver with absolute value1967 roman numerals3.5 in decimal formderivative of sin 2tdecimals fractions and percentageslog3 81what does 0x meancosx secx cosxsqrt 1-x 2-y 2298.95x 4y192 168 2121100 000 dollars in poundsprime factorization 50